2004
DOI: 10.1002/hec.881
|View full text |Cite
|
Sign up to set email alerts
|

The wage effects of obesity: a longitudinal study

Abstract: We use National Longitudinal Survey of Youth (NLSY) data to examine the effects of obesity on wages by gender. Sample means indicate that both men and women experience a persistent obesity wage penalty over the first two decades of their careers. We then control for a standard set of socioeconomic and familial variables but find that standard covariates do not explain why obese workers experience persistent wage penalties. This suggests that other variables -- including job discrimination, health-related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
309
4
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(342 citation statements)
references
References 17 publications
7
309
4
12
Order By: Relevance
“…The finding that the negative consequences of obesity on labor market outcomes are greater for females than for males is consistent with the findings from other studies analysing the impact of obesity on labour market outcomes (e.g., Baum and Ford, 2004;Cawley, 2004;Harper, 2000;Morris, 2007;Sargent and Blanchflower, 1994).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that the negative consequences of obesity on labor market outcomes are greater for females than for males is consistent with the findings from other studies analysing the impact of obesity on labour market outcomes (e.g., Baum and Ford, 2004;Cawley, 2004;Harper, 2000;Morris, 2007;Sargent and Blanchflower, 1994).…”
Section: Resultssupporting
confidence: 90%
“…Since previous studies have sometimes observed differences in the effect of body size on the wages of men and women (e.g., Averett and Korenman, 1999;Baum and Ford, 2004;Cawley, 2004), we provide estimates separately for men and women. In addition to estimating gaps between the obese (BMI ≥ 30) and persons of healthy weight (18.5 ≤ BMI < 25), we also conduct similar decomposition exercises for comparing persons who are overweight (25 ≤ BMI < 30) with persons of healthy weight.…”
Section: Linear Decompositionmentioning
confidence: 99%
“…Additionally, obese people are less likely to be employed, are perceived as less successful and are judged as possessing less leadership potential compared to normal weight colleagues [7,[31][32]. In comparison to normal weight employees, it has also been reported that obese people have lower starting salaries, are assessed as being less qualified, and work longer hours [32][33][34][35]. It should also be noted that discrimination towards obese women is greater than obese men, and this has also been identified in previous research examining workplace discrimination [31][32].…”
Section: Obesity Discrimination In the Workplacementioning
confidence: 99%
“…For example, Drewnowski and Specter (2004) attribute some of the high obesity rates of disadvantaged groups to the relatively low cost of energy-dense foods; similarly, the -weathering‖ hypothesis (Geronimus et al, 2006) emphasizes the cumulative impact of social or economic adversity and political marginalization. On the other hand, economists show that obese women receive a wage penalty (Averett and Korenman, 1996;Baum and Ford, 2004;Cawley, 2004), suggesting that excess weight reduces income-based measures of SES. Finally, unobserved factors could determine both SES and body weight.…”
Section: Socioeconomic Status and Obesitymentioning
confidence: 99%